Processing of herbal-based natural products and functional foods: a review - Chua, Hun Pin; Daniel, Nicholas (Penerbit Universiti Kebangsaan Malaysia, 2023)
The growing worldwide emphasis on health and wellness, leading to increased demand for natural plant-based ingredients in foods. This shift is driven by concerns over synthetic additives in processed foods, giving rise to the popularity of plant-based functional foods. The global functional food market is projected to reach $275.77 billion by 2025, with a surge in demand for plant-based immune-boosting products due to the COVID-19 pandemic. Malaysian herbs, with their rich history of culinary and traditional use, are gaining attention as functional ingredients. However, their incorporation into food products requires more advanced processing methods and research. Malaysia’s biodiversity offers untapped economic potential, and the country’s herbal industry is experiencing growth in exports and research investments. Herbal ingredients, containing active phytochemicals, are sometimes referred to as botanical substances and can be incorporated into formulations for functional foods. The review classifies herbal-based food products as herbal medicine, botanical food, or food-drug interphase (FDI). Herbal processing methods are crucial for ensuring the functionality of herbal-based products. Primary processing steps include sorting, cutting, drying, and grinding. Specific processing functions involve retaining active compound contents, enhancing effectiveness, reducing toxicity or side effects, and changing active compound properties or functions. The review also discusses the application of herb combinations in functional foods, highlighting the need for careful consideration of interactions between herbs and other components. Approaches to functional food development in Malaysia include refining existing products, creating new formulations, and integrating novel processing technologies. Future research directions include enhancing bioavailability and functionality of active compounds, exploring nanosystem technology, and incorporating nutrigenomics for disease prevention through dietary interventions.